ผลของอุณหภูมิออสเทนไนไทซิงในกระบวนการแพ็คคาร์เบอร์ไรซิงเพื่อใช้ผลิตมีดโต้ Effect of Austenitizing Temperature in the Pack Caburizing to Produce Big Knifes - หอมจะบก, วรรณา; ธรรมโชติ, ณรงค์ศักดิ์; ทาดี, นฤดม (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาผลของอุณหภูมิการอบเพิ่มคาร์บอนในกระบวนการแพ็กคาร์เบอไรซิง ของมีดโต้ที่ผ่านการตีขึ้นรูปจากเหล็กกล้าคาร์บอนตํ่า เปรียบเทียบกับมีดโต้ที่ผลิตจากเหล็กแหนบในท้องตลาด โดยเหล็กกล้าคาร์บอนตํ่าจะนำมาผ่านกรรมวิธีแพ็กคาร์เบอไรซิงที่อุณหภูมิ 900 950 และ 1,000oC เวลา 1.5 ชั่วโมง แล้วปล่อยให้เย็นตัวในอากาศ จากนั้นนำมาชุบแข็งที่อุณหภูมิ 780oC เวลา 20 นาที และอบคืนตัวที่อุณหภูมิ 180oC เวลา 1 ชั่วโมง สารแพ็กคาร์เบอไรซิงประกอบด้วยถ่านไม้ผสมกับสารเร่ง ได้แก่ CaCO3 BaCO3 และ Na2CO3 ผสมเข้าไปร้อยละ 10 โดยนํ้าหนัก จากนั้นทำการทดสอบความแข็ง แบบไมโครวิกเกอร์ ทดสอบแรงกระแทก และตรวจสอบโครงสร้างจุลภาค จากผลการทดลองพบว่า ที่อุณหภูมิ 950oC ของสาร BaCO3 และ Na2CO3 เหมาะสมในการผลิตมีดโต้มากที่สุด เพราะมีความแข็ง ที่ผิวสูงกว่าเหล็กแหนบ และมีความสามารถรับแรงกระแทกได้ดีกว่า สาเหตุที่เป็นเช่นนี้เพราะโครงสร้าง จุลภาคที่ผิวประกอบไปด้วยโครงสร้างมาเทนไซต์เป็นเนื้อพื้นและเม็ดคาร์ไบด์กระจายตัวอยู่ ส่วนภายใน โครงสร้างประกอบไปด้วยเพอร์ไลต์และเฟอร์ไรต์ Abstract The purpose of this research is to study the effect of carburizing temperatures on the hardness of the hardened big knives in pack carburizing process. The mechanical properties of the carburized and hardened big knives were compared to those of commercial hardened big knives made from leaf-spring steel. The experiment was conducted by forging big knives made of low carbon steel. They were then pack-carburized using wood charcoal mixing with CaCO3 BaCO3 and Na2CO3 as an energizer (10% by weight). The carburizing temperatures were 900, 950 and 1,000oC and carburizing times of 1.5 hours, and then were cooled by air. The austenitizing temperature was 780oC with a holding time of 20 minutes, followed by quenching in water. Finally, the big knives were tempered at 180oC for 1 hour. Micro-Vickers hardness testing, impact testing and microstructure inspection were carried out. The results of this experiment show that the carburizing temperature of 950oC of BaCO3 and Na2CO3 is suitable for the production of big knifes. It produces the surface hardness and impact energy higher than leaf spring knifes, because of the microstructure of the surface consists of martensite matrix with spheroid carbides dispersed, while the internal structure consists of pearlite and ferrite.